Degradable ultrathin high-performance photocatalytic hydrogen generator from porous electrospun composite fiber membrane with enhanced light absorption ability. Issue 16 (13th April 2021) - Wang, Qianyu; Zhang, Zhengmin; Liu, Lin; Bai, Lu; Bao, Rui-Ying; Yang, Ming-Bo; Yang, Wei
Abstract : A photocatalytic hydrogen energy generator was assembled with electrospun membrane. The unique internal structure enhances the light absorption ability and ensures the dispersion of photocatalysts, endowing the generator with excellent performance. Abstract : Poly(l -lactide) (PLA)/TiO2 /Pt composite fiber membrane with an internal porous channel structure was fabricated by skillfully tuning the breath figure mechanism and vapor-induced phase separation mechanism with solute and solvent matching via one-step electrospinning and applied in photocatalytic hydrogen production for the first time. The unique structure enhances the light absorption ability of the composite fiber and endows it with excellent photocatalytic hydrogen production performance. The hydrogen production efficiency of functional TiO2 particles loaded on the composite was increased 30 times compared with the efficiency of TiO2 particles in the aqueous solution, thus leading to 1.8 times increase in the hydrogen production capability and 5.8 times increase in the quantum efficiency compared with that of the TiO2 /Pt control sample. The composite fiber membrane was further assembled into an ultrathin (1.5 mm) and degradable hydrogen energy generator with a high power density of 47 W m −2 and a high UV luminous energy conversion rate of 92.8% under simulated sunlight.